Clinical manifestations of testicular adrenal rest tumor in males with congenital adrenal hyperplasia - Min Kyung Yu; Mo Kyung Jung; Ki Eun Kim; Ah Reum Kwon; Hyun Wook Chae; Duk Hee Kim; Ho-Seong Kim (Korean Society of Pediatric Endocrinology, 2015)
PurposeIn male patients with congenital adrenal hyperplasia (CAH), the presence of testicular adrenal rest tumors (TARTs) have been reported, however their prevalence and clinical manifestations are not well known. Untreated TARTs may lead to testicular structural damage and infertility. This study was conducted to investigate the prevalence of TARTs in male patients with CAH, and characterize the manifestations to identify contributing factors to TART.MethodsAmong 102 CAH patients aged 0-30 years, 24 male patients have been regularly followed up in our outpatient clinic at Severance Children's Hospital from January 2000 to December 2014. In order to reveiw the characteristics of TART patients, we calculated the mean levels of hormones during the 5 years before the time of investigation. Five patients underwent follow-up scrotal ultrasonography (US) after adjusting the dosage of glucocorticoids.ResultsTARTs were detected in 8 of the 13 patients (61.5%). The median age of TARTs diagnosis was 20.2 years with the youngest case being 15.5 years old. The mean serum level of adrenocorticotropic hormone (ACTH) was higher in the TARTs patient group compared to the non-TARTs group (P<0.05). The tumor size decreased in 3 cases, slightly increased in 1 case, and had no change in another case.ConclusionThe serum ACTH level might be associated with the growth promoting factor for TARTs, but the exact mechanism has not been clearly identified. Screening for TARTs using US is important in male patients with CAH for early-detection and prevention of ongoing complications, such as infertility.